2007
DOI: 10.1016/j.reprotox.2006.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Developmental exposure to endocrine disruptors and the obesity epidemic

Abstract: Xenobiotic and dietary compounds with hormone-like activity can disrupt endocrine signaling pathways that play important roles during perinatal differentiation and result in alterations that are not apparent until later in life. Evidence implicates developmental exposure to environmental hormone-mimics with a growing list of health problems. Obesity is currently receiving needed attention since it has potential to overwhelm health systems worldwide with associated illnesses such as diabetes and cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
179
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(191 citation statements)
references
References 22 publications
6
179
2
3
Order By: Relevance
“…These results suggest that attention should also be paid to T-cell differentiation in the female thymus in research on EDCs. Early onset of sexual maturation was reported in female mice delivered from dams treated with low doses of BPA (20 μg/kg/day) during gestation (Newbold et al, 2007;Honma et al, 2002). However, early onset of sexual maturation was not observed in mice neonatally treated with BPA (5 and 50 μg/kg) in the present study.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…These results suggest that attention should also be paid to T-cell differentiation in the female thymus in research on EDCs. Early onset of sexual maturation was reported in female mice delivered from dams treated with low doses of BPA (20 μg/kg/day) during gestation (Newbold et al, 2007;Honma et al, 2002). However, early onset of sexual maturation was not observed in mice neonatally treated with BPA (5 and 50 μg/kg) in the present study.…”
Section: Discussioncontrasting
confidence: 79%
“…Although increased body weight in mice after exposure to low doses of BPA (Rubin et al, 2001) or DES (Newbold et al, 2007) has been reported, decreased body weight was observed in male mice after neonatal exposure to low doses of BPA in this study. When the body weights of the male mice were compared to the background data we have on the same strain, the data of the control group in the present study were relatively high and those of the BPA groups were similar to the background data.…”
Section: Discussioncontrasting
confidence: 77%
“…Neonatal exposure to DES is reported to cause increase of uterine weight [30], decrease of body weight [31], and later in life, obesity [31] and uterine cancer [32]. One of the objectives of our work was to detect epigenetic changes in young mice to predict a future disease.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are genetic components for developing obesity. Lately, it has been hypothesized that exposure to endocrine disruptors, in utero and onwards, may play a role in the development of obesity and related diseases (Baillie-Hamilton 2002, Newbold et al 2007bNewbold et al , 2008. The molecular mechanisms behind a possible involvement of EDCs, so called obesogens, in obesity are poorly understood.…”
Section: Is Exposure To Edcs Involved In Development Of Metabolic Dismentioning
confidence: 99%